Mixing in Social Media. (29th April 2015) - Hogan, Bernie
This essay draws upon the social life of vinyl records as a means to consider social media as a set of many-to-many affordances rather than a suite of technologies. It defines affordances and draws upon their earlier history from cognitive science.